KOMUNIKASI DENGAN LINGKUNGAN EKSTERNAL DI SDN 01 WONOASRI: Komunikasi Sekolah dan Masyarakat - Melik Budiarti, S.Sos; Nanda Fajar Nugroho (STKIP Subang, 2025)
Schools and communities are inseparable components, each requiring a reciprocal relationship in various forms and implementation methods. Indeed, community participation in education is significant, including in the financing sector. In the current situation, this is a non-negotiable issue, as it is nearly impossible to provide good, quality education evenly, and the substantial costs involved are substantial, without community support and participation. Community relations for a school is a two-way relationship between the school and the community to discuss ideas and information useful for improving education. Similarly, communication exists between SDN 01 Wonoasri and its community, especially the school's neighborhood. During the community service program at SDN 01 Wonoasri, the importance of community relations with the school was discussed.